STUDENTSâ PERCEPTION OF BLENDED LEARNING ENVIRONMENT IN CALL COURSE: ADVANTAGES, LIMITATIONS, AND SUGGESTIONS FOR IMPROVEMENT - Rombe, Kristasia (Jurnal Dinamika Pendidikan, 2014)
This study aims to investigate the perception of the students English Teaching Study Program (ETSP), Christian University of Indonesia. The participants were 64 students who participated in CALL course conducted in the odd semester of 2013/2014 aca-demic year. The quantitative data were collected using questionnaire and analyzed by using Microsoft Excel 2010. The qualitative data were collected using interview and an-alyzed descriptively. The findings revealed that the students responded positively to the use of BL to improve their vocabulary and grammar mostly through writing activities. The students also perceived by using BL, their computer skill and interest were devel-oped. Regarding the advantages, connectivity was indicated as a major problem fol-lowed by social isolation. As a result of the problems addressed, increasing the number of computer labs and training were suggested by the majority of students. Based on the findings, it is recommended to ETSP to continue with BL by increasing the number of computer labs and training for students.Keywords: BL, CALL, course, perception